Vignettes From a Lifetime of Studying Performance - Schechner, Richard (LEARNing Landscapes, 2020)
In this commentary, summarized from a recent interview, the author shares insights and memories from a career devoted to drama and performance studies. He enthusiastically recounts events, initiatives, and collaborations that have helped sustain his lifelong passion for performance.